A Comprehensive Analysis of Beekeeping Risks and Validation of Biosecurity Measures against Major Infectious Diseases in Apis mellifera in Europe - Alessandra De Carolis; Adam J. Newmark; Jieun Kim; Junxia Song; Marco Pietropaoli; Veronica Manara; Andrea Gyorffy; Joseph Cazier; Giovanni Formato (Agriculture, 2024)
Background/Objectives: In a collaborative effort, FAO, the International Federation of Beekeepers’ Association “Apimondia”, the Appalachian State University, and the Istituto Zooprofilattico Sperimentale del Lazio e Toscana (IZSLT), the FAO Reference Centre for Animal Health and Food Security Discipline Apiculture, health, and biosecurity, designed an online international survey (“Knowledge, Awareness and Practice”-KAP) as a risk assessment tool to validate biosecurity measures able to prevent and control the main honeybee (Apis mellifera subsp.) infectious diseases. Methods: The KAP survey was disseminated through various channels for 14 months (January 2019–March 2020). Beekeepers’ knowledge on nosemosis, American foulbrood (AFB), and European foulbrood (EFB) management was assessed. Beekeepers’ attitudes were investigated by asking them to provide a score called “Acceptance by beekeepers”. Results: Of the 410 respondents, the majority of them (68.3%, n = 252) were from Europe. European beekeepers (n = 252) considered “Highly acceptable” the following practices: removing combs that show signs of dysentery and feeding colonies for nosemosis; the quick identification and management of affected hives for American foulbrood and European foulbrood. Instead, the following practices were considered as not acceptable by beekeepers: for nosemosis, the use of antibiotics and sampling of hive debris for early detection; for American foulbrood and European foulbrood, the shook swarm, the destruction of the whole apiary, as well as their treatment with antibiotics. Conclusion: This study demonstrated the validity of the present “Knowledge, Awareness and Practice” (KAP) survey to validate the best practices for the main infectious honeybee diseases, considering the pragmatic point of view of beekeepers. Sustainable practices for disease control are preferred by the European beekeepers. While having an adequate knowledge base for the early detection of the investigated honeybee diseases, European beekeepers tend to be aware of the health status of their hives, embracing advanced, practice-oriented training. Authors highlight that the selection of practices and their validation should be revised on a regular basis, to be adapted in a timely manner to the current infectious honeybee disease situation, in order to build up a resilient and effective stock of practices.